WORKING-CLASS VOICES: SONGS, REPERTOIRES AND MUSICALPRACTICES IN THE CHILEAN LABOR MOVEMENT - Navarro López, Jorge; Ubilla Espinoza, Lorena (Revista de Historia Social y de las Mentalidades, 2025)
Music was an essential part of the cultural practices which politicized organized working class in the early decades of the 20th century. Through the analysis of the songs published by the working-class press and the songbooks which collected them afterwards, this article delves into the sonic repertoire of socialist- communists and anarchists, presenting differences and similarities. Alongside poetry and drama, song became one of the most extended uses when socializing and critically occupying public spaces. In this sense, we pose that this exercise in composition and performance allowed them to spread proposals of an alternative culture drawing on common feelings of exploitation and emancipation utopias.